Applying performance measures to support informed decision making at an operational level - Moreira, Madalena; Tjahjono, Benny; Julião, Jorge (Cranfield University Press, 2013)
Performance Measurement Systems (PMS) have commonly been applied to evaluate and reward performances at managerial levels, especially in the context of supply chain management. However, evidence suggests that the effective use of PMS can also positively influence the behaviour and improve performance at an operational level. The purpose of the study described in this paper is to develop a conceptual framework that adopts performance measures for ex-ante decision-making at an operational level within the supply chain. A case study at Coca-Cola Enterprises has been carried out and as a result, a conceptual framework of the PMS has been developed.
Keywords: Performance measures; Performance Measurement System; supply chain; decision-making; flexibility